Effect of Honey and Vitamin C on Growth and Carcass Traits of Broiler Chicken During Summer Season - Begum, Most Saba; Bithi, Tahera Yeasmin; Khatun, Mst Afroja; Islam, Md Rafiul (Research in Agriculture Livestock and Fisheries, 2025)
A study was undertaken to investigate the dietary effect of different levels of honey and vitamin C on growth performance and carcass traits of commercial broilers. The study was conducted at the poultry farm of HSTU, Dinajpur during the period from 26 April to 23 May, 2018. A total of 96-day-old broiler chicks (Cobb 500) were randomly and equally distributed to 4 treatments having 3 replicates of 8 birds each. The birds were grouped as T0, T1, T2, and T3 groups with ordinary water (control), 2.5 ml honey/L of drinking water, 5 ml honey/L of drinking water, and 125 mg vitamin C/L of drinking water, respectively. Body weight gains, Feed Conversion Ratio (FCR), mortality (%), and meat yield traits were recorded. Feed intake (g/bird) was almost similar (P>0.05) among the dietary treatment groups. Body weight gain (g) and FCR were significantly (P<0.05) differed among the dietary treatment groups. The highest body weight gain (g) was significantly (P<0.05) higher in T2 (1659.02g±6.92), followed by T1 (1630.75g±8.40), T3 (1595.10g±9.50) and T0 (1468.01g±5.40), respectively. The lowest FCR was found in T2 (1.35±0.00) and the highest FCR in T0 (1.48±0.01), the intermediate in T1 (1.36±0.01) and T3 (1.39±0.01), respectively. It was found that there was significant (P<0.05) difference among the dietary treatment groups in the case of live weight (g), carcass weight (g), dressing percentage (%), breast weight (g), thigh weight(g), liver weight(g), but there was almost similar (P>0.05) in case of different body part’s weight. Based on the result, it could be concluded that 5ml of honey/L of drinking water can be used in broiler diet as a growth promoter, and it may also serve as an antioxidant during stress conditions. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 187-202